Variable glucagon metabolic actions in diverse mouse models of obesity and type 2 diabetes - Wu, Yuqin; Chan, Andrea Y.; Hauke, Jana; Htin Aung, Okka; Foollee, Ashish; Cleofe, Maria Almira S.; Stölting, Helen; Han, Mei-Ling; Jeppe, Katherine J.; Barlow, Christopher K.; Okun, Jürgen G.; Rusu, Patricia M.; et al. (Molecular metabolism, 2024)
Objective - The study aimed to investigate the effects of glucagon on metabolic pathways in mouse models of obesity, fatty liver disease, and type 2 diabetes (T2D) to determine the extent and variability of hepatic glucagon resistance in these conditions. - Methods - We investigated glucagon's effects in mouse models of fatty liver disease, obesity, and type 2 diabetes (T2D), including male BKS-db/db, high-fat diet-fed, and western diet-fed C57Bl/6 mice. Glucagon tolerance tests were performed using the selective glucagon receptor agonist acyl-glucagon (IUB288). Blood glucose, serum and liver metabolites include lipids and amino acids were measured. Additionally, liver protein expression related to glucagon signalling and a comprehensive liver metabolomics were performed. - Results - Western diet-fed mice displayed impaired glucagon response, with reduced blood glucose and PKA activation. In contrast, high-fat diet-fed and db/db mice maintained normal glucagon sensitivity, showing significant elevations in blood glucose and phospho-PKA motif protein expression. Acyl-glucagon treatment also lowered liver alanine and histidine levels in high-fat diet-fed mice, but not in western diet-fed mice. Additionally, some amino acids, such as methionine, were increased by acyl-glucagon only in chow diet control mice. Despite normal glucagon sensitivity in PKA signalling, db/db mice had a distinct metabolomic response, with acyl-glucagon significantly altering 90 metabolites in db/+ mice but only 42 in db/db mice, and classic glucagon-regulated metabolites, such as cyclic adenosine monophosphate (cAMP), being less responsive in db/db mice. - Conclusions - The study reveals that hepatic glucagon resistance in obesity and T2D is complex and not uniform across metabolic pathways, underscoring the complexity of glucagon action in these conditions.